Ladybug Girl and Bingo - Soman, David; Davis, Jacky 1966- (New York : Dial Books for Young Readers, 2012)
Lulu, who likes to dress in a ladybug costume, goes camping with her parents, brother, and dog Bingo.
a"Companion to: Ladybug Girl"--Cover.
Keywords: Camping -- Fiction; Dogs -- Fiction